Robust optimization of the efficient syngas fractions in entrained flow coal gasification using Taguchi method and response surface methodology. (23rd February 2017) - Hou, Jinxiu; Zhang, Jinchun
Abstract: The robustness of the efficient syngas (ES, H2  + CO) fraction in an entrained flow coal gasification is very important to the stable operations of some downstream applications. This study presents the details about the robust optimization of the ES fraction in a typical entrained flow coal gasification, Shell coal gasification process (SCGP). In this study, Taguchi method combined with response surface methodology (RSM) was used. A series of numerical experiments in Aspen plus were carried out according to the operations of a demonstration SCGP gasifier. After systematic statistical analysis, the ES fraction was robust optimized using Nelder–Mead algorithm. The results show that integrating Taguchi and RSM method provides an effective solution to the robust optimization of the ES fraction. Oxygen to coal ratio (O/C) is the "robust factor" which significantly affects not only the ES fraction but also the fluctuation in it. The ES fraction increases at first and decreases later with increasing O/C, but the fluctuation in it is just the opposite. Pressure (P) is the "regulation factor" which has no effects on the ES fraction but can change the fluctuation. Thus adjusting it to a moderate level is helpful for further suppressing the fluctuation. Stream to coal ratio (S/C) is the "secondary factor" which has slightly effect on the ES fraction and the fluctuation. The optimal robust solutions of the control parameters, P, S/C and O/C, are 3.69 MPa, 0.05 and 0.61 kg/kg respectively. Under this condition, the fraction of ES is about 98.42% with 0.18% fluctuation, which presents good robustness. Highlights: The fraction of efficient syngas (H2  + CO) in an entrained flow coal gasification was robust optimized. Taguchi method combined with response surface methodology was used. The influence of oxygen to coal ratio, pressure and stream to coal ratio on the fraction of (H2  + CO) was investigated.